EVALUATION OF THE APPLICATION OF THE ASSURE MODEL BASED ON THE COUNTENANCE STAKE MODEL ON RUKHSAH MATERIAL IN BUILDING EFFECTIVE LEARNING - Tarsono, Tarsono; Fitriani, Fitriani; Muchlis, Abdul; Nupus, Dian; Azizah, Nurul; Rosyida, Nadya Ilma (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
The learning process determines student success in learning, so teachers need to build effective learning that supports these achievement goals. This study aims to analyze the evaluation of the application of the ASSURE model based on the Countenance Stake model on rukhsah material in building effective learning at SMP Hikmah Teladan. This research uses a qualitative approach using a descriptive analysis method. The results and conclusions of this study show that the application of the ASSURE model to rukhsah material in  SMP Hikmah is exemplary based on the results of evaluation using the countenance stake model has been applied very well and supports building effective learning; the average good student learning outcomes show this.